Sikurma: Development Of A Google Apps Script–Based Document Repository Information System For Optimizing Digital Archive Management In Higher Education - Indra Surya Permana; Ade Sutriyono; Citra Setyo Dwi Andhini; Sabili Muhammad Azka (Jurnal Media Computer Science, 2026)
Strategic document management for accreditation and Key Performance Indicator (KPI) reporting poses significant challenges for higher education institutions due to unstructured digital archives and high implementation costs of commercial Electronic Document Management Systems (EDMS). This research aims to design, develop, and evaluate SIKURMA (Document Repository and Archive Management Information System), a low-cost and easily replicable document repository solution based on Google Workspace. The development method employs a prototyping approach with user-centered design orientation, including stages of needs analysis, system design, development using Google Apps Script, and evaluation through the DeLone & McLean Information System Success Model framework. The research results demonstrate a functional SIKURMA prototype capable of dynamically displaying file lists from Google Drive, equipped with hierarchical navigation features, global and per-folder search capabilities, and a simple spreadsheet-based authentication system. Quantitative evaluation involving 35 lecturer respondents from various study programs shows that all system success hypotheses were accepted with high significance levels. The system successfully achieves zero-cost infrastructure by utilizing available Google Workspace, making it easily replicable by various higher education work units. SIKURMA proves to offer practical and efficient solutions for optimizing digital document governance in higher education institutions with limited resources